Synthesis and characterisation of (C4N2H12)(UO2)2(PO3H)2(PO2(OH)H)2: a three dimensionally connected actinide framework. - Doran, M; Walker, S; O'Hare, D (2001)
The material (C4N2H12)(UO2)2(PO3H)2(PO2(OH)H)2 (MUPH-1) has been prepared hydrothermally; it is a three dimensional structure consisting of four intersecting elliptical shaped one-dimensional channels, the largest channel has dimensions of 13.1 x 7.2 A.